(untitled) (Journal of Nepal Physical Society, 2024)
In this study, carbon was prepared by carbonization of ZnCl2 activated wood of Buddleja Paniculata at 700 °C and the activated carbon was used in the preparation of the electrodes of supercapacitors. Physical properties of the activated carbon were analyzed by using X-ray Diffraction (XRD), Raman spectroscopy, Fourier Transform Infrared Spectroscopy (FTIR), N2 adsorption-desorption isotherms, Scanning Electron Microscopy (SEM), and Energy Dispersive X-ray Spectroscopy (EDS). These analyses revealed a high carbon concentration (96.7 %) and a dominant amorphous carbon in the sample. The calculated Brunaeur-Emmet-Teller (BET) surface area of activated carbon was 1326 m2 g−1 with a high volume of microporous structures. The electrochemical properties of the prepared supercapacitor electrodes using activated carbon were analyzed by cyclic voltammetry (CV) and galvanostatic charge-discharge (GCD) tests in a three-electrode system. They exhibited excellent electrochemical double layer capacitance (EDLC) behavior and a specific capacitance of 117.58 Fg−1 at 1 Ag−1 . The above investigation indicates that the activated carbon of Buddleja Paniculata can be a low-cost supercapacitor electrode material.